Analisis Faktor-Faktor Yang Mempengaruhi Struktur Modal Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Kusumaningati, Iip Dyah; Salsa Septiyana Putri (PT. Karya Inovatif Nusantara, 2024)
This study aims to determine the effect of Company Size, Profitability, Asset Structure on Capital Structure listed on the Indonesia Stock Exchange in 2020 – 2022. Capital structure is part of the dependent variable, while the independent variables include company size, profitability and asset structure. The population in this study are manufacturing companies in the consumer goods industry sector, the food and beverage sub-sector, which are listed on the Indonesia Stock Exchange in 2020 – 2022. The sampling technique used was purposive sampling and a sample of 12 companies was obtained. Data were collected from the annual reports of each company concerned and analyzed using multiple regression analysis. The results of the study show that company size partially has no significant effect on capital structure. This is evidenced by its significance value, which is 0.449 > 0.05. Profitability partially has no significant effect on Capital Structure, this is evidenced by its significant value, namely 0.745 > 0.05. And Asset Structure has no significant effect on Capital Structure, this is evidenced by its significance value of 0.002 < 0.05.